Architectural temperance : Spain and Rome, 1700-1759 - Deupi, Victor (London ; New York : Routledge, Taylor & Francis Group, 2015)
'Architectural Temperance examines relations between Bourbon Spain and papal Rome (1700-1759) through the lens of cultural politics. With a focus on key Spanish architects sent to study in Rome by the Bourbon Kings, the book also discusses the establishment of a program of architectural education at the newly founded Real Academia de Bellas Artes de San Fernando in Madrid. Victor Deupi explores why a powerful nation like Spain would temper its own building traditions with the more cosmopolitan trends associated with Rome; often at the expense of its own national and regional traditions. Through the inclusion of previously unpublished documents and images that shed light on the theoretical debates which shaped eighteenth-century architecture in Rome and Madrid, Architectural Temperance provides an insight into 18th century Spanish architecture in English'--
Includes bibliographical references (pages 184-207) and index.
Keywords: Real Academia de Nobles Artes de San Fernando; Architecture and society -- Spain -- History -- 18th century; Architecture -- Spain -- History -- 18th century; Architecture -- Spain -- Italian influences; Architecture -- Study and teaching -- Spain -- Madrid; Architecture -- Study and teaching -- Italy -- Rome; ARCHITECTURE / History / Contemporary (1945-).; ARCHITECTURE / Buildings / Public, Commercial & Industrial; ARCHITECTURE / Methods & Materials